THE INFLUENCE OF PANCASILA EDUCATION LEARNING ON INCREASING SOCIAL AWARENESS AND NATIONALISM OF STUDENTS - Nur Hidayat (CV. RADJA PUBLIKA, 2025)
This study aims to determine the influence of Pancasila Education learning on increasing students' social awareness and nationalism. Using a quantitative approach with a survey method, this study involved 100 high school students who had participated in Pancasila Education learning. The instrument used was a closed questionnaire that was validated and tested for reliability. The results of the study show that Pancasila Education learning has a positive and significant influence on both variables, namely social awareness and nationalism. Students who participated in learning with an interactive and contextual approach showed a higher level of empathy, social concern, and a sense of love for the homeland. Regression analysis shows that Pancasila Education learning contributes 42.3% to social awareness and 48.1% to student nationalism. These findings confirm that Pancasila Education not only functions as an instrument of normative knowledge, but also as a medium for the formation of social character and national identity. Therefore, a more applicable and reflective learning approach needs to be developed so that Pancasila values can be internalized more optimally in students' lives.